Butterflies (Lepidoptera: Papilionoidae) in Fef Forest, Tambrauw District, Southwest Papua - Rawati Panjaitan; Via Dolorosa; Yance de Fretes; Keliopas Krey (Postgraduate, University of Mataram, 2025)
Butterflies of the superfamily Papilionoidae, or true butterflies, play a crucial role as indicators of ecosystem health and pollinators, and in the Papuan biogeographic region. The diversity of butterflies depends on habitat quality. A high ecosystem composition will support high butterfly diversity. Data on butterfly diversity is not yet available from the Fef forest in Tambrauw, making this research crucial. The composition of butterflies will also determine the condition of the forest, as they are used as bioindicators of forest quality. The forests in the Fef District are classified as secondary and primary forests. The research was conducted over six days of observation, from 8:00 AM to 5:00 PM. The study used a scan sampling method along predetermined transects. Butterflies and dragonflies were captured using insect nets, then photographed and identified. This study aims to understand the diversity and species richness in the region and determine the composition of forest richness in Fef. The research in the Ibu forest in the Fef District identified 96 butterfly species (1.87 individuals). The butterflies found were spread across six transects observed over six days. Transects were established in secondary and primary forest habitats. The Shannon-Wiener index for butterfly diversity was high (H’=3.98).